FED up with fat tubes. - Chalamala, B.R (IEEE spectrum)
Field emission displays (FED) offer the best and brightest of two display worlds: the bright picture of bulky cathode-ray tube devices and the trim flat-panel picture of liquid-crystal displays. The similarities and differences between FED and CRT are briefly mentioned. The principles of FED operation, and the fabrication of the emitter array and anode, are described